The Relationship of Pedagogical Practices on Biology Online Learning With Learning Outcomes at High School During The Covid-19 Pandemic - Oktavianus Fian Dega; Yuswa Istikomayanti; Nugroho Aji Prasetiyo (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
This study aims to determine the relationship between pedagogic practice of biology online learning and student learning outcomes in class XI SMAN 9 Malang. This research was conducted from 02, October 2021 to 07, October, 2021 at SMAN 9 Malang. This research includes ex post facto research with quantitative research using survey mode with correlation analysis techniques in surveys, information is collected from respondents using questionnaires or questionnaires. Data analysis techniques in this study are collecting data, reducing data, presenting data, verifying and drawing conclusions. The results of this study are Biology online learning pedagogic practices have a significant relationship with student learning outcomes during the Covid-19 pandemic, but are at a very low level. This is indicated by a significance value of 0.434 where 0.575 > 0.05. In addition, based on the results of a simple correlation analysis obtained a correlation value of 0.103, which means the direction of the relationship is positive. Based on the results of research and discussion, there is a significant relationship between online learning pedagogic practices and student learning outcomes during the Covid-19 pandemic which is at a very low level. Because in the online learning process there are shortcomings, namely the lack of maximum student involvement, lack of learning time, teachers have difficulty determining whether students do assignments independently or not, so teachers must work as much as possible to adapt to the online learning process but these obstacles can be overcome properly due to assistance and motivation of various parties.